The pyramidal organizational structure of jurisdictional institutions in Peru and abroad - Miranda Canales, Manuel Jesús (2007)
This article explains, very briefly, the pyramidal jurisdictional structure of Peru and some foreign countries like: Argentina, Chile, Bolivia, Brazil, the United States, Spain, Italy and France, making reference to the support or control systems that conforms the Judicial System in each one of these countries.